2011
DOI: 10.6017/ital.v30i3.1768
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting University Library Website Design

Abstract: Existing studies have extensively explored factors that affect users’ intentions to use university library website resources (ULWR); yet little attention has been given to factors affecting university library website design. This paper investigates factors that affect university library website design and assesses the success of the university library website from both designers’ and users’ perspectives. The findings show that when planning a website, university web designers consider university guidelines, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…Usability studies take time and money, and given the large Library Home Page Design 23 number of potential designs, it is prohibitive to study all of the various design options and services that a library Web site could offer. Yong-Mi Kim (2011) noted that libraries often lack sufficient training and resources to support the design process. In addition, Kim found that academic library Web designers often review other library Web sites when developing their own designs, because the design of other libraries exerted a mimetic force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usability studies take time and money, and given the large Library Home Page Design 23 number of potential designs, it is prohibitive to study all of the various design options and services that a library Web site could offer. Yong-Mi Kim (2011) noted that libraries often lack sufficient training and resources to support the design process. In addition, Kim found that academic library Web designers often review other library Web sites when developing their own designs, because the design of other libraries exerted a mimetic force.…”
Section: Resultsmentioning
confidence: 99%
“…questionnaires, usability tests, and focus groups), one method is to examine multiple library Web sites to determine common practices. Yong-Mi Kim (2011) argued that library Web design should involve not solely usability testing but also the review of other library sites as well. Employing content analysis to study a large number of Web sites to determine Web design best practices is well-established.…”
Section: Library Home Page Designmentioning
confidence: 99%
“…She understood the pros, cons, pitfalls, and gray tape involved in that process. Kim (2011) affirmed the value of input from immediate stakeholders in addition to that of the "secondary sources" (p. 100), i.e., the webmasters and consultants who would identify technical flaws and contribute to design. Three undergraduate student workers rounded out the team.…”
Section: Defining Parametersmentioning
confidence: 99%
“…User-friendly navigation without library jargon was the first priority. Kim (2011) noted that Web site design and Web site performance are closely correlated and that user orientation is essential. "If a Web site helps users complete their tasks, they are likely to use (it)" (p. 99).…”
Section: Establishing Goalsmentioning
confidence: 99%
See 1 more Smart Citation